SOCIAL ENTREPRENEURSHIP AND CHALLENGES IN INDIA: REVIEW - Dr. Mohd. Rizwan Ahmad (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Social entrepreneurship is a start-up and entrepreneurial approach in which, finance, and implement solutions to social, cultural, or environmental issues. This definition can be extended to a wide range of organizations varying in size, purpose, and creeds. The concept of rising social entrepreneurship in India and around the world has helped to serve society more meaningfully than ever before, along with the fullest living of the spirit of entrepreneurship. Social entrepreneurship is not a modern idea but in recent times the concept's positioning has risen to new heights. This paper is a detailed study of social entrepreneurship, including the conceptual framework of social entrepreneurship and its operation. This research paper also discusses the different challenges faced by social entrepreneurs and puts forward their proposals to improve the overall social entrepreneurship / entrepreneurship situation in India. More research paper explores correlation and distinction between social and economic entrepreneurship, as well as describing social entrepreneurship. The paper also discusses the principles from an entrepreneurial point of view, such as social needs and technological developments. Over recent years, social entrepreneurship has expanded its reach and significance and this paper also covers both fields. Finally, this research paper also illustrates how social entrepreneurship can alter or impact the social system and social fibres in India and other developed nations at the bottom of the pyramid stage